Efficacy of Serratiopeptidase After Impacted Mandibular Third Molar Surgery: A Split-Mouth Randomized Controlled Trial - Arwa M. Dahak; Abdullah H. Farhan; Ali A. Al-Moanan; Shatha Q. Al-Ja'afari (University of Science and Technology, Sana’a, Yemen, 2026)
Background: Surgical extraction of impacted mandibular third molars is frequently associated with postoperative complications such as trismus, facial edema, and pain, primarily due to inflammatory responses. Conventional management using corticosteroids and nonsteroidal anti-inflammatory drugs (NSAIDs) is effective but may cause adverse systemic effects with prolonged use. Serratiopeptidase, a proteolytic enzyme with anti-inflammatory and analgesic potential, has been investigated as a safer adjunctive therapy, though evidence remains limited. This study aimed to evaluate the clinical efficacy of serratiopeptidase in reducing postoperative complications following impacted mandibular third molar surgery. Methods: A triple-blind, randomized controlled clinical trial using a split-mouth design was conducted in twelve healthy patients requiring bilateral surgical removal of impacted mandibular third molars. Each patient served as their own control, with one extraction site receiving conventional therapy alone (amoxicillin, metronidazole, and diclofenac sodium) and the contralateral site managed with the same regimen supplemented by oral serratiopeptidase. Assessments of trismus, facial edema, and pain were performed preoperatively and on the 2nd, 3rd, and 5th postoperative days. Data were analyzed using repeated-measures analysis of variance (RMANOVA), with significance set at P <0.05. Results: All 12 participants completed the trial, yielding 24 surgical sites for analysis. Trismus improved significantly over time in both sides (P <0.001), with no significant interaction effect between treatment and time. Facial edema across all types demonstrated significant reduction across time points (P <0.001), but between-group comparisons showed no significant differences. Pain scores were consistently lower in the serratiopeptidase side, with significant main and interaction effects (P <0.001), confirming superior analgesic benefit. Conclusion: Serratiopeptidase is a valuable adjunct to conventional postoperative therapy in mandibular third molar surgery, particularly for pain reduction. However, its effects on trismus and facial edema are limited, with recovery patterns largely comparable to those observed with standard care. These findings support the use of serratiopeptidase as a safe, effective adjunct to conventional therapy for improving patient comfort.